Cover Feature: Structural Features of Porous CoFe Nanocubes and Their Performance for Oxygen‐involving Energy Electrocatalysis (ChemElectroChem 18/2020). Issue 18 (24th August 2020) - Jo, Sujin; Noh, Sunguk; Wee, Kyung‐Ryang; Shim, Jun Ho
Abstract : The Cover Feature shows that microporous CoFe‐200 nanocubes (mean pore diameter, d ≈1.2 nm) are beneficial for the oxygen evolution reaction (OER) because of the improved active site densities despite their larger diffusion path, whereas microporous/mesoporous CoFe‐550 ( d ≈35.6 nm) favors the oxygen reduction reaction (ORR) by enabling the mass transport of oxygen through the catalyst. More information can be found in the Article by J. H Shim and co‐workers .